Corporate Ethical Branding on YouTube: CSR Communication Strategies and Brand Anthropomorphism. Issue 1 (2nd January 2017) - Wen, Jing (Taylor); Song, Baobao
ABSTRACT: Even as ethical branding gains increasing prominence, the effectiveness of specific communication and branding strategies remains somewhat unexplored. A content analysis was conducted to examine Fortune 500 companies' corporate social responsibility (CSR) advertisements and user comments on YouTube. The results showcase that involvement strategy of CSR communication is considered to be the most effective on social media, because social media as a communication platform is conversational and consumers expect to engage in more integrative and personalized relationships with brands on such platforms. CSR messages on social media should demonstrate brand personality through brand anthropomorphism. Using more first-person pronouns to refer to the brand, incorporating more human representations, and using more imperative verbs will achieve more positive user comments. The findings further suggest that the success of ethical branding on social media lies in more interactive and engaging communications as well as branding strategies.